The Effect of Ethical Leadership, Organizational Politics Perception, and Moral Courage on Internal Whistleblowing - Ilham Maulana Saud; Nida Shintya Maulida; Ietje Nazaruddin (Jurnal Akuntansi Keuangan dan Bisnis, 2022)
This study examines the effect of ethical leadership on internal whistleblowing through organizational politics perception as a mediating variable. In addition, this study also investigates the role of moral courage as a moderating variable. This study was conducted at the local government in Tabalong Regency, South Kalimantan Province, Indonesia. The sample selection used the purposive sampling method, and a total of 267 valid responses was obtained as samples. The data were collected employing the questionnaire survey method. The data were then processed utilizing SEM-PLS through the SmartPLS 3.0 application. The study results found that ethical leadership had a direct or indirect positive effect on internal whistleblowing. Meanwhile, moral courage was not proven to moderate the negative relationship between organizational politics perception and internal whistleblowing. This study also uncovered that organizational politics perception had a negative effect on internal whistleblowing.